(untitled) (Journal of Advanced Research in Social Sciences, 2021)
The political arena in Cuba has had a direct impact on the development of the media throughout the country’s history. Therefore, it is necessary to know the updated status of the Cuban media system in the last stage (2018-2019) nowadays. This article shows the main transformations of the Cuban media system, based on the analysis of the historical process experienced on the island since 1959. The current press model is classified based on the theoretical analysis of The Four Theories of the Press. The methodology used allowed us to carry out a study of 50 issues of the Granma newspaper - chosen for its great influence on the Cuban society, with a sample of 1031 news items on different topics. The analysis helped to determine that the content of the Cuban government media its core and main aims are used to spread the socialist ideas and concepts. Both the content analysis and the historical process revealed that the media in Cuba continues to be controlled by the Government and maintains its social character, which makes it possible to relate the current media system with the old Soviet press model, although the current scenario, marked by the access to Internet and the appearance of new independent digital media not recognized by the government, creates the bases for the conception of a socialist alternative to the social responsibility model.